PERAN GADGET TERHADAP KREATIVITAS WARGA MASYARAKAT DI DESA MAGERU KIDUL RT 02/RW 01 TAHUN PELAJARAN 2021/2022 - Afifah, Siti Nur (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
Abstract The purpose of this research was to find out how the community's creativity in using cell phones in the vilage of mageru Kidul RT 02 RW 01. This research was conducted in mageru Kidul vilage RT 02 RW 01 Plumbungan Karangmalang sragen. This research is a qualitative deskriptive research. Data collection techniques are through interviews, observasion, dokumentation,and home visits. In this study,the research subjec were 3 community members in mageru Kidul vilage. The validity of the data in the study is triangulation of sources and triangulation of data.qualitative data analysis has an inductive nature,such us based on the analysis of the data obtained and then the relasionship pattern is developed through the following steps : data reduktion,data presentation,results or drawing conclusions. The result of the study exsplained that creativity in the use of celluler phones in the modern era is very helpful and facilitates work, especially in the economic and education sectors .it is hoped that this can be an example for others to be wiser in using cell phones and also to be creative in ultilizing this very sophisticated litle device. Keywords : creativity in using cell phones in the economic and educational sector